A legal and economic analysis of the concept of anticipatory breach under the CISG - Murtuza, Seema (Riga Graduate School of Law, 2021)
Contractual remedies are traditionally available after the breach of a contract, but can a party suspecting non-performance prior to the date of performance entitled to seek for remedies? The United Nations Convention on the International Sale of Goods (CISG), regulates the doctrine of anticipatory breach in Articles 71-73, outlining the circumstances in which an anticipatory breach is deemed to occur and the remedies available to the aggrieved party. The Convention entitles the innocent party to the right to suspend or avoid but it contains unambiguous terms in need for interpretation. Additionally, the doctrine of anticipatory breach begs the questions of economic efficiency, a fundamental aim of the CISG. In that regard, this research paper uses a legal doctrinal and economic analysis of law to interpret Article 71-2 and determine whether it reduces the transaction cost of the parties
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Contract law